Intensity and spatial extent of droughts in southern Africa - (:unkn) unknown (My University, 2005)
The standardized precipitation index allows for monitoring the intensity and spatial extent of droughts at different time scales. We used it to do a retrospective analysis of the spatial extent of droughts in Southern Africa (South of 10°S), from 1901 to 1999. Accordingly, the 8 most severe droughts at the 6-month scale (October–April) for the summer rainfall region of Southern Africa ended in 1916, 1924, 1933, 1949, 1970, 1983, 1992 and 1995. At the 2-year scale, they ended in 1906, 1933, 1983, 1984, 1992, 1993, 1995 and 1996. Areas affected by those droughts ranged from 3.4 to 2 106 km2. Eight of those 12 years are El Niño years. Preliminary data indicates that 2001/2002, 2002/2003 and 2003/2004 experienced severe droughts at a number of scales. This confirms the increase in the spatial extent of drought in Southern Africa since the 1970's due to stronger ENSO Southern African rainfall relationship
Keywords: African Research